A professziótól a professzionális intézményrendszerig: A professziókat megalapozó átfogó struktúrákról (Szociológiai Szemle, 2024)
Sociologists seem to have lost interest in investigations concerning the theoretical framework for the analysis of the professions. Recent studies have not contributed significantly to the theoretical paradigms of the mid-1970s. They have concentrated rather on providing detailed descriptions of the single professions and their national differences. This paper proposes an approach to the theoretical study of the professions, which contrasts their functional differentiation with N. Luhmann’s analyses of social subsystems. It suggests that professional subsystems be defined by the respective populations which professionally use the adequate binary codes in their communications. The concept of a social subsystem will thus be replaced by that of the system of professional institutions which is, in many respects, close to the concept of ‘professions’ as used by sociologists. The paper presents a revised version of the author’s theory on the system of professional institutions.